Study on the Process of Preparing Zinc and Silver-Loaded Sepiolite and Its Antimicrobial Ability - Liu, Jing (Asian Journal of Chemistry, 2013)
The inorganic antibacterial agents (single metal ions), process for preparing double ion-type inorganic antibacterial agents was studied by using sepiolite as carrier and silver ions and zinc ions as antibacterial components. By determining the content of antibacterial ions loaded in sepiolite using atomic absorption spectroscopy, the effect of sodium phosphate in processing sepiolite and the loaded capacity of two ions in different processing methods were compared. The results showed that the antibacterial ion contents can be significantly improved with sodium phosphate pretreatment, followed by acid modification of sepiolite. When the initial concentration ratio of Zn2+ and Ag+ was 10:1 in sepiolite in this experiment, the content ratio of the two ions was more than 8:1. Thus, the content of Zn2+ loaded in sepiolite was increased and that of Ag+ decreased. The prepared sepiolite loaded with silver and zinc ions had good antibacterial property and resistance to discoloration. There was certain relationship between absorption of Ag+ and Zn2+ ions onto sepiolite and the contents of two kinds of antibacterial ions in sepiolite, but the correlation was weak.